Modeling of the Malaysian crude oil system - Ahmad Mohd Yusof; Maznah Banu Mohamed Habiboo Raman; Zulkifli Mohd Nopiah (Penerbit Universiti Kebangsaan Malaysia, 2013)
As a part of energy planning, Malaysia is developing a long term energy model as a tool to manage its natural resources. The purpose of paper is to present the preliminary results obtained from optimizing the initial model. Being a net exporter of crude oil, Malaysia exports its crude oil and compressed natural gas, as well as imports crude oil and coal to satisfy its own energy needs. At the earlier stage of model development, the crude oil system is cast as an energy flow network model tracing its flow from extraction sources or imports; and following the flow through conversion and transformation processes; and, ultimately, distribute its end products to the final demand sectors. The preliminary results of the model indicate that the extraction and the import of several petroleum products show erratic behavior and, thus, such irregularity should be overcome before adding further energy systems to the model.